Calculation & simulation of fractionation-based separation methods for airborne particles - Poh, Shao Yi (Nanyang Technological University, 2021)
Field Flow Fractionation (FFF) is a separation method first proposed in the mid-1960s and gradually perfected through in a very performant technique. FFF is one of the most well-known separation methods with high versatility (Schimpf et al., 2000). In FFF, different fields (or gradients) applied transversally across the channel, i.e. normal onto the fluid flow, can be used to separate particles present in the flow, depending on the differences in some of their intrinsic properties to control the separation of Particles. (Qian et al., 2014). However, FFF has never or hardly have been done where the carrier for the channel flow is air. COMSOL is a multiphysics Finite Element Analysis (FEA) simulator that can analyze even the combined effect of coupled fields, and thus can determine how airborne particles flow or move under the influence of the applied transversal fields (thermal/electrical/flow). The initial aim was to perform COMSOL simulations in order to find which applied field is more effective for size-based separation of airborne particles. However, due to time constraints and the limitations of the software version/license, COMSOL simulations could be carried out only for two uncharged particles but each with conductivity, permittivity and diameter values of 0.31 S/m, 5*10˗10 F/m and 5 microns for the first particle and 0.25 S/m, 5*10˗10 F/m and 1.8 microns for the second one, respectively. However, it was considered that both particles were made of the same material, i.e. had the same density of 1050 kg/m^-3. The simulation targeted to separate these two different particles when using a transversal dielectrophoretic (DEP) force resulted from the application of an A.C. nonuniform electric field across the channel. The obtained results presented in this Report show that any of the intrinsic characteristics of the particles (permittivity, conductivity, size/diameter) can be used to separate them using FFF.